Optimization of Dialogic Patrol of the Bogor Police Sabhara Unit to Prevent Prostitution Activities Under the Guise of Contract Marriage in Cisarua District - Pradana, Rizky Revin (Police Studies Review, 2024)
The background of this research is prostitution practice behind contract marriage in Cisarua, Bogor with customers from Middle East. This practice was being famed through a French documentary. It is known that this practice has been occurring for eight years. This practice suits element of Indonesian Law (UU) No. 21 Year 2007 and the system of the marriage violates UU No. 1 Year 1974. In this case, assessing the optimization of dialogic patrol activity (kegiatan patroli dialogis) as the preventive action is needed. The objective of this thesis is to describe and analyze the implementation, influencing factors, and the effect of communication in optimizing Polres Bogor’s dialogic patrol activity in preventing prostitution behind contract marriages in Cisarua. This thesis used the concept of Standard Operational Procedure Patroli Dialogis Satuan Sabhara Polres Bogor, George R. Terry’s management theory with 6M, and Lasswell’s communication theory which answers Who Says What in Which Channel to Whom with What Effect? to analyze the problem. Field research qualitative approach is also used in this thesis. The datas were gathered through observations, interviews, and being involved in the activity with data analysis technique (data reduction, presentations, taking conclusion and doing validation with data triangulation). The result shows that the dialogic patrol activity has not been held optimally, some of the substances in the SOP is not done entirely which were shown from factors affecting the dialogic patrol activity. These factors inhibits the activity and does not bring any change which results in the poor deliver of messages and the way the messages being delivered. This thesis recommends prioritizing the prostitution behind contract marriage as the target, utilizing technology and in-between media to communicate and coordinate with the related parties.